CHARACTER EDUCATION BASED ON LOCAL WISDOM IN LEARNING RIAU MALAY CULTURE - Naratiba, Raudhoh; Suroyo, Suroyo; Fatmasari, Rhini (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2024)
Learning local content builds national character, because it pays attention to environmental characteristics and local culture. This study aims to determine the application of character education to students based on local wisdom in the Riau Malay learning process. This research is ethnographic and qualitative with the principal, 7 class teachers, and students as subjects. The research instrument consists of observation, interviews, documentation. The results of this study have been carried out well based on local wisdom in Malay culture learning at SDN 183 Pekanbaru including being religious, honest, disciplined, social care, responsibility, environmental care, independent and respectful.